The Role of Social Media in Supporting Open and Distance Learning - Hayu Lusianawati; Mumammad Kharizmi; Fauziatul Halim; Syahrianti Syam; Widiharto Purnomo (P3M IAI Nusantara Batang Hari, 2024)
Today's education has developed very rapidly, also supported by technological developments which are increasing day by day. It is undeniable that people are competing with each other to gain knowledge wherever and whenever. Advances in technology are really very helpful in the educational process. With the development of technology, of course, this is not too bothered, because technology has solved this problem. Through technology, various social media appear that can support the learning process, both directly and distance and open learning. The purpose of this study is to determine the role of social media in supporting distance and open learning. The method used in this research is a quantitative research method with a research design in the form of a survey. The data in this study were obtained by filling out a questionnaire on the Google form link. The results of this study are that the role of social media in supporting distance and open learning plays a very important role. Because social media has a variety of applications that support distance and open learning. The conclusion from this study is that social media plays a very important role in supporting distance and open learning. Through social media, students can carry out online learning without having to be in the same place as the teacher so that they can study anytime and anywhere, because this is a hallmark of distance and open learning. The limitation in this study is that the researcher only conducted research at the school level. The researcher also hopes that further researchers will expand research to a higher level and the researcher also hopes that in the future other researchers will emerge who can develop this research and focus on one part of social media.